(untitled) (EAAE Annual Conference Proceedings, 2025)
The skyline of many Chicagoan streets is being progressively disrupted by the appearance of a new generation of buildings whose shape, far from striving for an adequate composition and a balanced urban landscape, only aims to get the maximum number of square meters to other for sale or rent. The massive and occasionally peculiar silhouette of new building developments or extension of pre-existing premises is increasingly present in well-known neighborhoods such as Magnificent Mile or the Loop, where the high demand for housing has led developers to seek to optimize their earnings by maximizing the profitability of a given plot of land. Behind us is a whole generation of skyscrapers with a strong iconic quality, attained not only through the maximization of the number of stories, but also and fundamentally through their form and materiality. The three towers of the St. Regis designed by Jeanne Gang after the meaningful success of her design for the Aqua Tower, also in Chicago, seem to be among the last examples of a gilded age of which the Willis Tower and, mostly, the John Hancock Center, both by Skidmore, Owens and Merrill, and Fazlur Kahn and Bruce Graham, are the most prominent examples. All these buildings gave the city of Chicago an unmistakable skyline of great personality and unquestionable interest, capable of attracting visitors from all over the world to a city whose greatest tourist attraction is the architecture it has been able to produce at diferent periods of its history. However, this struggle for square footage is nothing new in the history of this American metropolis. In fact, it is at the genesis itself of the skyscraper typology, born precisely in Chicago mostly as a consequence of the fire which devastated the city in 1871. The new layout of the downtown streets made them wider, reducing the size of the resulting plots and requiring an increase in the number of stories in order to restore to the owners the surfaces they owned before the fire. Hence, buildings renowned as the nowadays disappeared Home Insurance Building by William Le Baron Jenney, relying on the technological development of means and materials, only aimed at restoring the profitability of the premises or even increasing it.